Association between Phospholipase Production by Malassezia pachydermatis and Skin Lesions - Cafarchia, C. (American Society for Microbiology, 2004)
An evaluation was made of the phospholipase activities of Malassezia pachydermatis strains isolated from healthy dogs versus those from dogs with dermatitis and otitis. A high percentage of strains of M. pachydermatis obtained from lesion sites (93.9%) produced phospholipase, compared to the strains obtained from healthy skin of the same dog with localized lesions (41.4%) and healthy dogs (10.6%).